2013
DOI: 10.1007/s10637-013-9999-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of AT-101 with cisplatin and etoposide in patients with advanced solid tumors with an expanded cohort in extensive-stage small cell lung cancer

Abstract: Background A phase I, dose-escalation study of AT-101 with cisplatin and etoposide was conducted to determine the maximum tolerated dose (MTD)/recommended phase 2 dose (RP2D), safety and pharmacokinetics in patients with advanced solid tumors, with an expanded cohort in patients with extensive-stage small cell lung cancer (ES-SCLC) to assess preliminary activity. Methods In the dose escalation portion, increasing doses of AT-101 were administered orally BID on days 1–3 along with cisplatin on day 1 and etopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…This is significant because genetic inhibition of gene expression presents significant challenges in a clinical setting. LDH is a promising therapeutic target for a variety of malignancies (22,25,27,30,33), and systemic inhibition of LDH is clinically feasible and can be well tolerated. Additional anti-LDH pharmacotherapies are in development along with strategies to more precisely target specific organs and cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significant because genetic inhibition of gene expression presents significant challenges in a clinical setting. LDH is a promising therapeutic target for a variety of malignancies (22,25,27,30,33), and systemic inhibition of LDH is clinically feasible and can be well tolerated. Additional anti-LDH pharmacotherapies are in development along with strategies to more precisely target specific organs and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the properties of gossypol appear to be dose and cell type specific. Gossypol also effectively inhibits cell differentiation in several types of malignancy (19,34,35) and is being investigated as a potential cancer therapy (25,27,30). Because of these properties, we wanted to determine whether gossypol would also be effective at inhibiting TGF-␤-induced myofibroblast differentiation and may therefore represent a possible treatment for pulmonary fibrosis.…”
mentioning
confidence: 99%
“…Gossypol and its derivatives inhibit the growth of cancer-cell lines and show anticancer activity in animal models 252 . Although earlier trials with racemic gossypol were not successful, a single enantiomer of gossypol (called AT-101) is now in clinical trials in patients with different forms of cancer 253 . Newer analogues of gossypol are also being tested in cancer 254 , but it remains to be seen whether or not they will be successful.…”
Section: Protein Protein Interactions Protein Protein Interactions Amentioning
confidence: 99%
“…It is currently being investigated in phase I/ II clinical trial as an antagonist of Bcl-2 family proteins [2,10,28,32,35]. However, the clinical trial results showed that AT-101 administration did not extend overall survival or improved the progression-free survival [2,35].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that AT-101 exhibits broad activity against various types of cancers, such as breast, prostate, lung, lymphoma, and head and neck cancers [20,23,25,38,44]. Clinically, phase I/II trials evaluating safety and efficacy of AT-101 as a single agent or in combination with other anticancer drugs are ongoing in refractory small cell lung cancer, metastatic castration-resistant prostate cancer, to name a few [2,10,28,32,35].…”
Section: Introductionmentioning
confidence: 99%